Analisis Zodiac dan Horoscope dalam Kitab Abu Ma’syar Al Falaki; At-Thowali’ Al-Hadsiyyah Li Ar-Rijal Wa An-Nisa Perspektif Astronomis - Ismail, Ismail Ismail (Institut Agama Islam Negeri (IAIN) Syekh Nurjati Cirebon, 2024)
Astrology can be defined as a science that studies the position of celestial bodies (zodiac) that is considered to have an effect on human life (horoscope). Astrology is a science whose validity or validity is still controversial because it has not been scientifically proven, even though there are several things that are references in Astrology, basically it is also not contrary to Astronomy. One of the books of Astronomy by Jafar ibn Muhammad ibn Umar Abu Mashar al-Balkhi is Abu Ma'syar Al Falak; At-Thowali' Al-Hadsiyyah Li Ar-Rijal Wa An-Nisa (Zodiac and Horoscope). The methodology uses descriptive qualitative, literature review and literature related to Astrology and makes the book of Abu Ma'syar the main object, with supporting references. The horoscope and horoscope as part of the study of Astrology, reviewed from the perspective of Abu Ma'syar Al Falaki and Astronomical. According to Abu Ma'syar, the Zodiac is divided into 12 types. While from an Astronomical perspective, there are 13 types of zodiac, there is an additional constellation of Ophichius (Snake holder). There are 7 celestial bodies that are used as standard horoscopes, namely: Sun (Syams), Moon (Qamar), Mercury (Utharid), Venus (Venus), Mars (Miriikh), Jupiter (Jupiter), and Saturn (Saturn). This, results in certain zodiac signs having the same horoscope. The disposition of the horoscope consists of 4 types, namely fire, earth, air, and water. Regarding the presentation and processing of data, the book of Abu Ma'syar uses Jumali numbers while astronomically uses observation data in units of degrees.Barbarslot adalah salah satu situs resmi slot deposit 5000, 5rb dan depo 5k terbaru dengan beragam permainan terbaik tahun 2025.